Variação de atributos funcionais e sua influência no desempenho de espécies arbóreas reintroduzidas em áreas degradadas - Fernandes, Janaína de Fátima (2018)
The study of tree species functional traits can be a useful tool in the context of forest restoration in degraded environments. That is because understanding relationships between different traits and their interactions with abiotic components of degraded environments can allow stronger generalizations and predictions on the performance of different reintroduced species in these environments. The present thesis is composed of three independent chapters that have the same objective of evaluating variations of functional attributes and how they determine the performance of reintroduced tree species in degraded areas. In the first chapter, we investigated native tree species reintroduced in a degraded Brazilian cerrado area. We evaluated changes in functional attributes over plant initial development and the relationships between them. We found that the largest changes in functional attributes occurred in the initial months, and that environmental filters must have influenced strongly these changes since the beginning of species development. In the second chapter, we evaluated the influence of functional traits and growing conditions on the survival and growth of plants in the same study area of the first chapter, in two different stages of species development in the field. We found that, at each stage, different functional attributes contributed to survival and growth, and this can be attributed to different environmental limiting factors at each stage. In the third chapter, we carried out a study in another area which was in restoration process, where soil presented a fertility gradient. We evaluated whether variations in functional attributes within species were a direct response to different levels of soil nutrients or due to the different sizes of plants. We found that variations in most functional attributes were related only to plant size, which grew more vigorously in more fertile soils. In general, we showed that functional attributes varied over the initial development of species, were related to the environmental conditions of degraded areas and to plant size, determining the performance of species in these areas. Functional traits can be useful for predicting plant response to the environmental conditions in degraded areas and can help in the planning of more efficient forest restoration strategies.